Pengaruh Penggunaan Gemini AI pada Perencanaan Proyek Biologi terhadap Kreativitas Peserta Didik di SMA : Penelitian - Rosi Ramadhani; Relsas Yogica; Zulyusri; Fitri Olvia Rahmi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
ThisPstudy waspconducted to determineethe extent to whichhthe use of Gemini AI in designing biology projects can influence student creativity in project-based learningm(PBL) at the highsschool level. Theeresearch method used was a quasi-experimentalmmodel with a Pretest-Posttest Control Group Design. The study population was all students of grade X PhasmE at SMA Negeri 1 Lubuk Alung. The sample consisted of two classes: X.E1 as the control group with 36 students, and X.E3 as the experimental group with 35 students. The research instrument was a creativity questionnaire. Data analysis was carried out using a t-test and obtained a significanceevalue of 0.02 which isssmaller than 0.05, indicating a significant difference between groups. In conclusion, the useeof Gemini AIlin the planning stage of biology projects has beenpproven topsignificantly increase student creativity.